2017
DOI: 10.3389/fped.2017.00102
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Problems in Parents of Children with Congenital Heart Disease

Abstract: This review will provide a concise description of mental health problems in parents of children with a (non-syndromic) congenital heart disease (CHD) during different stressful periods. Predictors of these problems and also implications for clinical practice will be mentioned. Having a child with CHD can be very stressful for parents, who have to face overwhelming emotions and also extra physical, financial, and other practical challenges. Parental distress has been reported in 30–80% of parents and appears no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 28 publications
3
74
0
4
Order By: Relevance
“…Learning of the condition prenatally however may mean the pregnancy becomes more difficult because families anticipate that they may face suffering and difficulty after the child's birth (Janvier, Farlow, & Wilfond, 2012). Although knowledge of a severe defect prior to a child's birth is typically considered beneficial to parents, some researchers have questioned this assumption because studies have shown that prenatal diagnosis is associated with increased parental distress (Kolaitis, Meentken, & Utens, 2017;Lawoko & Soares, 2006;Öst, Nisell, Frenckner, Mesas Burgos, & Öjmyr-Joelsson, 2017). In a study comparing reactions of family members who received a diagnosis of congenital heart disease in their child, investigators found that both fathers and mothers who received the diagnosis prenatally were more depressed, while those who received the diagnosis postnatally were more stressed (Bevilacqua et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Learning of the condition prenatally however may mean the pregnancy becomes more difficult because families anticipate that they may face suffering and difficulty after the child's birth (Janvier, Farlow, & Wilfond, 2012). Although knowledge of a severe defect prior to a child's birth is typically considered beneficial to parents, some researchers have questioned this assumption because studies have shown that prenatal diagnosis is associated with increased parental distress (Kolaitis, Meentken, & Utens, 2017;Lawoko & Soares, 2006;Öst, Nisell, Frenckner, Mesas Burgos, & Öjmyr-Joelsson, 2017). In a study comparing reactions of family members who received a diagnosis of congenital heart disease in their child, investigators found that both fathers and mothers who received the diagnosis prenatally were more depressed, while those who received the diagnosis postnatally were more stressed (Bevilacqua et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The initial diagnosis is a stressful time for parents of children with CHD and diagnosis is increasingly more common in the prenatal period [38, 39]. During prenatal counseling, parents of children with CHD place a greater importance on QOL of their future child, including the number of lifetime interventions and physical limitations than their fetal cardiologist [40].…”
Section: Discussionmentioning
confidence: 99%
“…For children with severe and chronic illnesses is confirmed that the parents are mentally stressed (7).…”
Section: Introductionmentioning
confidence: 96%
“…For example parental distress has been reported in 30-80% of parents with congenital heart disease and 40% report a need for psychosocial care (7).…”
Section: Introductionmentioning
confidence: 99%